Antimicrobial Resistance and Genotypic Diversity of Campylobacter Isolated from Pigs, Dairy, and Beef Cattle in Tanzania - Kashoma, Isaac P.; Kassem, Issmat I.; Kumar, Anand; Kessy, Beda M.; Gebreyes, Wondwossen; Kazwala, Rudovick R.; Rajashekara, Gireesh (Frontiers in Microbiology, 2015)
Foodborne Campylobacter infections pose a serious threat to public health worldwide. However, the occurrence and characteristics of Campylobacter in food animals and products remain largely unknown in Tanzania. The objective of this study was to determine the prevalence, antibiotic resistance, and genetic profiles (sequence types, STs) of Campylobacter isolated from feces of pigs and dairy and beef cattle in Tanzania. Overall, 259 (~ 30%) of 864 samples were positive for Campylobacter spp, which were detected in 32.5%, 35.4%, and 19.6% of the pig, dairy, and beef cattle samples, respectively. Multiplex PCR analysis identified 64.5% and 29.3% of the Campylobacter isolates as C. coli and C. jejuni, respectively. The majority (91.9%) of the isolates from pig samples were identified as C. coli, while C. jejuni accounted for 65.5% of the isolates from cattle. Antimicrobial susceptibility testing using the disk diffusion assay and the broth microdilution method revealed resistance to: ampicillin (70% and 76%), gentamicin (1.8% and 12.6%, respectively), streptomycin (65.8% and 74.8%), erythromycin (41.4% and 48.7%), tetracycline (18.9% and 23.4%), and ciprofloxacin (14.4% and 7.2%). Resistance to nalidixic acid (39.6%), azithromycin (13.5%), and chloramphenicol (4.5%) was determined using the disk diffusion assay only, while resistance to tylosin (38.7%) was quantified using the broth microdilution method. Multilocus sequence typing of 111 Campylobacter isolates resulted in the identification of 48 STs (26 C. jejuni and 22 C. coli) of which 7 were novel (6 C. jejuni and 1 C. coli). Taken together, this study revealed the high prevalence, genetic diversity and antimicrobial resistance of Campylobacter in important food animals in Tanzania, which highlights the urgent need for the surveillance and control of Campylobacter in this country.